Spectrophotometric Determination of Tartrazine, Riboflavine and Carmoisine in Drinks by Zero-order Spectrophotometric Method using Determinant Calculation and First Derivative Spectrophotometric Method - Kara, Derya (Asian Journal of Chemistry, 2016)
Two very simple spectrophotometric methods are described for resolving binary and ternary mixtures of the food colorants tartrazine, carmoisine and riboflavine using the absorption and the first derivative spectra. Calibration graphs are up to 103 mg L-1 of of tartrazine (E-102), 30.2 mg L-1 of carmoisine (E-122) and 30 mg L-1 of riboflavine (E101). Standard deviations of 0.4, 0.7 and 1.4% were obtained for nine standards of 15 mg L-1 of tartrazine, 15 mg L-1 of riboflavine and 10 mg L-1 of carmoisine, respectively. In this study, concentrations of tartrazine (T), riboflavine (R) and carmoisine (C) in binary and ternary mixtures are calculated by Cramer (determinant) method using absorption spectra. T, C and R were also simultaneously determined in their binary mixtures by first derivative spectrophotometry. The method was applied to different drinks. This method was satisfactorily used for determining synthetic mixtures of these colorants in different ratios. It was successfully applied over three commercial products containing the three dyes and did not require any separation step.